1984
DOI: 10.1007/bf00377386
|View full text |Cite
|
Sign up to set email alerts
|

Age and hunting success in the brown pelican: influences of skill and patch choice on foraging efficiency

Abstract: Age-related differences in the foraging efficiency of piscivorous birds may be the results of differences in foraging skill, patch usage, or both. Brown pelicans were observed while foraging around a small Caribbean island. Areas where the birds fed were subdivided into small, homogeneous subunits (patches), and the bird's foraging success and patch use were noted and analyzed using multivariate techniques. Adult birds were found to be better at capturing prey under all conditions than were juveniles, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…We have shown that adult Great Grebes forage more efficiently than juveniles, an age-related feature common in other birds (Orians 1969; Morrison et al 1978;Searcy 1978;Burger 1980;Schnell et al 1983;Brandt 1984;MacLean 1986;Carl 1987;Arnqvist 1992;Papakostas et al 2005). Foraging efficiency is supposed to increase with age and experience (Buckley and Buckley 1974;Morrison et al 1978;Schnell et al 1983;Brandt 1984), and foraging inefficiency of juveniles has been suggested as contributing to their higher early age mortality (Lack 1954;Ashmole 1963;Weimerskirch 2002).…”
Section: Foraging Efficiencymentioning
confidence: 96%
See 3 more Smart Citations
“…We have shown that adult Great Grebes forage more efficiently than juveniles, an age-related feature common in other birds (Orians 1969; Morrison et al 1978;Searcy 1978;Burger 1980;Schnell et al 1983;Brandt 1984;MacLean 1986;Carl 1987;Arnqvist 1992;Papakostas et al 2005). Foraging efficiency is supposed to increase with age and experience (Buckley and Buckley 1974;Morrison et al 1978;Schnell et al 1983;Brandt 1984), and foraging inefficiency of juveniles has been suggested as contributing to their higher early age mortality (Lack 1954;Ashmole 1963;Weimerskirch 2002).…”
Section: Foraging Efficiencymentioning
confidence: 96%
“…Foraging efficiency is supposed to increase with age and experience (Buckley and Buckley 1974;Morrison et al 1978;Schnell et al 1983;Brandt 1984), and foraging inefficiency of juveniles has been suggested as contributing to their higher early age mortality (Lack 1954;Ashmole 1963;Weimerskirch 2002). Foraging efficiency could therefore be expected to be under strong selection pressure, which means that individuals able to learn fast have high survival rates (Morrison et al 1978).…”
Section: Foraging Efficiencymentioning
confidence: 98%
See 2 more Smart Citations
“…Parental efficiency is thus expected to increase with age through increased foraging abilities of the parents in the European shag, Phalacrocorax aristotelis, for instance (Daunt et al, 1999). However, evidence of improved foraging ability with age in free-ranging individuals is scarce [but see Brandt (Brandt, 1984) for the brown pelican, Pelecanus occidentalis], and the precise mechanisms by which such improvement may occur remain unclear. These mechanisms may be easier to highlight when individuals are subjected to strong environmental conditions (Daunt et al, 2007;Lescroël et al, 2009).…”
Section: Introductionmentioning
confidence: 99%